2019
DOI: 10.26533/jmd.v2i2.370
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Experiential Marketing Terhadap Keputusan Pembelian Smartphone Xiaomi

Abstract: Penelitian ini dilatar belakangi oleh semakin besarnya nama perusahaan Xiaomi di dalam pasar smartphone khususnya di Indonesia. Experiential marketing adalah salah satu strategi pemasaran yang saat ini digunakan oleh banyak perusahaan termasuk Xiaomi. Strategi pemasaran yang tidak sekedar menawarkan produk saja, tetapi juga dengan melakukan pendekatan pengalaman dengan memerhatikan unsur (sense, feel, think, act dan relate). Penelitian ini dimaksudkan untuk mengetahui dan menganalisa pengaruh dari sense, feel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…Based on the results of this research hypothesis, the accepted hypothesis is in accordance with research that has been conducted by previous researchers who explained that Experiential Marketing influences Purchase Decisions made by (Syahadat, 2018) and (Budiarto & Pancaningrum, 2019). (Shahadat, 2018) conducted research on the Effect of Experiential Marketing as a marketing strategy at Starbucks Coffee on purchasing decisions, the results of research conducted by (Syahadat, 2018) found that the experiential marketing variable had a positive and significant effect on purchasing decisions at Starbucks Coffee.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on the results of this research hypothesis, the accepted hypothesis is in accordance with research that has been conducted by previous researchers who explained that Experiential Marketing influences Purchase Decisions made by (Syahadat, 2018) and (Budiarto & Pancaningrum, 2019). (Shahadat, 2018) conducted research on the Effect of Experiential Marketing as a marketing strategy at Starbucks Coffee on purchasing decisions, the results of research conducted by (Syahadat, 2018) found that the experiential marketing variable had a positive and significant effect on purchasing decisions at Starbucks Coffee.…”
Section: Discussionsupporting
confidence: 88%
“…(Shahadat, 2018) conducted research on the Effect of Experiential Marketing as a marketing strategy at Starbucks Coffee on purchasing decisions, the results of research conducted by (Syahadat, 2018) found that the experiential marketing variable had a positive and significant effect on purchasing decisions at Starbucks Coffee. (Budiarto & Pancaningrum, 2019) also conducted research that discussed the effect of Experiential Marketing on Xiaomi smartphone purchasing decisions, the results obtained from this study were that there was also a positive and significant influence between experiential marketing on Xiaomi smartphone purchasing decisions.…”
Section: Discussionmentioning
confidence: 90%
“…Brand identity is very important for companies, many researchers observe how to improve brand identity or what factors affect it. One of them is Budiarto (2019) revealed that experiential marketing affects purchasing decisions on smartphones [3]. The research focused on one of the smartphone products, while our research focused on the café industry.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Several previous studies have revealed that experiential marketing programs can influence purchasing decisions [3], customer satisfaction [4], customer loyalty [5][6] [7][8], brand image [9][10], revisit intention [11], and repurchase intention [12], however, no one has yet examined its effect on brand identity. In fact, in the opinion of Sankaran (2010) stated that if the company can provide a good experience to customers, it will be able to provide positive emotions to these customers so that it can increase product identity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Experiential marketing adalah salah satu konsep dari marketing modern dengan strategi-strategi pemasaran yang dilakukan dengan pendekatan secara emosional kepada konsumen (Budiarto & Pancaningrum, 2020). Experiential marketing merupakan konsep pemasaran yang telah dilakukan sejak dahulu hingga saat ini, karena pendekatan ini dinilai efektif dan sesuai dengan perkembangan zaman, teknologi (Yuliawan & Ginting, 2016).…”
Section: Pendahuluanunclassified